ANALYSIS ON THE STRATEGY AND IMPLEMENTATION OF DIGITAL TECHNOLOGY IN THE XYZ COMPANY - Wijaya, Septihani Michella; Budiman, Bellinda; Johan, Livia; Laurent, Margaret; Ie, Mei (International Journal of Application on Economics and Business, 2023)
The agricultural sector grew by 2.19% y-o-y in 2020 and contributed to Indonesia's GDP of 15.46%. Agribusiness potential is one of the largest contributors to Indonesia's GDP. Not only that, the Covid-19 pandemic has forced the acceleration of digital transformation in business activities. This encourages the need for digital transformation for XYZ company to be able to survive in the agro-industry business. The application of Information and Communication Technologies (ICT) and the use of the Internet of Things (IoT) are challenges and opportunities for companies to carry out digital transformation. The existence of obstacles and challenges that need to be overcome by the company requires handling carried out in strategic and systematic steps in order to survive in the market. XYZ's challenges in implementing digital transformation lie in the level of penetration and understanding of digital technology, the use of technology that has not been maximized, and intense competition. Where XYZ also has digital opportunities because Indonesian people are starting to switch to online shopping patterns.